THE INFLUENCE OF READING HABITS OF PAI TEXT BOOKS ON STUDENT LEARNING OUTCOMES AT SMA NEGERI 4 TAKALAR (International Conference on Social and Islamic Studies, 2022)
The purposes of this study were: 1) To describe the habit of reading PAI textbooks in SMA Negeri 4 Takalar, 2) To analyze the learning outcomes of PAI in SMA Negeri 4 Takalar, 3) To analyze the influence of the habit of reading PAI textbooks on student learning outcomes in SMA Negeri 4 Takalar. This research is a quantitative research with the type of ex post facto research with a simple linear regression research design. This research was conducted at SMA Negeri 4 Takalar. The sample in this study were 70 people. The instruments used in this study were the habit of reading PAI textbooks and test item sheets. The analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of the descriptive study obtained that the habit of reading PAI textbooks  for students at SMA Negeri 4 Takalar was in the moderate category, namely 65.71%, while the learning outcomes in the subject of Islamic Religious Education students at Negeri 4 Takalar were in the moderate category, namely 68 , 57 %. The calculation results obtained (tcount) = 3.549 while (ttable) = 1.995 for a significance level of 0.05%, because tcount is greater than ttable, it can be concluded that Ho is rejected and H1 is accepted. This means that there is an effect of the habit of reading PAI textbooks on the learning outcomes of students at SMA Negeri 4 Takalar. The implications of this research are: (1) for school principals to always pay more attention to students so they are able to study well, (2) for educators to continue to improve students' book reading habits by carrying out actions that trigger the development of book reading habits (3 ) for students to practice improving and applying the habit of reading books in every subject, especially in Islamic Religious Education so that student learning outcomes increase and also have an impact on their daily lives, (4) for future researchers if they want to do similar research should add other independent variables that support learning outcomes in Islamic Religious Education subjects.